STUDY ON THE ROLE OF GLOBALIZATION IN GROWING THE MOBILITY OF INTERNATIONAL STUDENTS IN THE LAST DECADE - Alina MARCUTA; Ramona Elena ANGHEL; Cristiana TINDECHE; Mihaela ROSU; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
One of the advantages of the globalization process is that of ensuring the circulation of young people at the global level, ensuring their access to existing learning resources in countries with a developed and recognized higher education system worldwide. Starting from the existing data in various international, community and national databases, in this work we proposed to analyze the mobility situation of undergraduate, master's and doctoral students from the period 2012-2022, with the aim of identifying the countries that are on the first places in the world both in terms of student entry flows and their exit flows. The analysis was carried out starting from indicators such as the number of students leaving for studies, the number of students entering for studies, their growth rate, but also the mobility rate at the entrance or the mobility rate at the exit. The data were processed and analyzed with the help of statistical methods, thus being able to formulate conclusions regarding the situation of student mobility from the last decade, given the identification of solutions regarding the provision of future flows of students for higher education institutions, under the conditions that, globally, the population aged between 20-24 will decrease in areas such as Europe or North America. Under these conditions, the educational institutions recognized for the quality of the programs offered will be able to attract students from countries in Asia or Africa, countries in which both the share of the young population and mobility have increased in the last five years. Among these countries are India, with an increase of over 100%, Vietnam with an increase of 95% or China, with an increase of 33%.